2022
DOI: 10.3389/fcell.2022.877892
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Oligosaccharides Regulate the Occurrence and Development of Enteritis in a Human Gut-On-a-Chip

Abstract: Past studies on the protective effects of chitosan oligosaccharides (COS) on inflammatory bowel disease (IBD) commonly rely on animal models, because traditional cell culture systems couldn’t faithfully mimic human intestinal physiology. Here a novel human gut-on-a-chip microsystem was established to further explore the regulatory effects of COS on the occurrence and development of human enteritis. By constructing an intestinal injury model caused by dextran sodium sulfate (DSS) on the chip, this study proved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…This intestine chip model is able to form intact intestinal F I G U R E 8 Mimicking treatment and therapy of intestinal disease using intestine chips. (A) Protective effect of gut bacteria and antibiotics in EIEC-induced and immune cell-associated intestinal injury, reproduced with permission of 45 Copyright 2016 PNAS and (B) protective effect of COS in intestine inflammation induced by DSS and pathogenic E. coli 11773, reproduced with permission of 94 Copyright 2022 Frontiers Media SA epithelium with barrier functions and normal blood vessels or lymph vessels and is also suitable for mimicking other organs such as the lung and brain. A comprehensive intestine emulation should comprise epithelial cells, endothelial cells, and all other cells present in the simulated target microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This intestine chip model is able to form intact intestinal F I G U R E 8 Mimicking treatment and therapy of intestinal disease using intestine chips. (A) Protective effect of gut bacteria and antibiotics in EIEC-induced and immune cell-associated intestinal injury, reproduced with permission of 45 Copyright 2016 PNAS and (B) protective effect of COS in intestine inflammation induced by DSS and pathogenic E. coli 11773, reproduced with permission of 94 Copyright 2022 Frontiers Media SA epithelium with barrier functions and normal blood vessels or lymph vessels and is also suitable for mimicking other organs such as the lung and brain. A comprehensive intestine emulation should comprise epithelial cells, endothelial cells, and all other cells present in the simulated target microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging characterization of the intestine chip. (A) Differential interference contrast (DIC) micrograph showing intestinal basal crypt (red arrow) and villi (white arrow) formed by human Caco‐2 intestinal epithelial cells and immunofluorescence image showing a horizontal cross‐section of F‐actin (green) and DAPI stained nuclei (blue), reproduced with permission of 45 Copyright 2016 PNAS; immunofluorescence images showing (B) a vertical cross‐section of MUC2 (red), F‐actin (yellow) and DAPI stained nuclei (blue), reproduced with permission of 60 Copyright 2019 Springer Nature; (C) a horizontal cross‐section and vertical cross‐sections of NHE3 (green), reproduced with permission of 61 Copyright 2021 Elsevier; (D) ZO‐1‐positive Caco‐2 cells (green) and PECAM‐1‐positive HUVECs (carmine), reproduced with permission of 72 Copyright 2022 Springer Nature; (E) WGA (left, green) and occluding on intestinal epithelial cells (right, red), reproduced with permission of 94 Copyright 2022 Frontiers Media SA and (F) the invasion of CRC cells (green) from epithelium into endothelium (red), reproduced with permission of 47 Copyright 2021 Elsevier…”
Section: Coupling Intestine‐on‐a‐chip With Analytical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, some studies have found that functional oligosaccharides such as inulin-derived FOS can also increase the colonization sites of probiotics in the intestinal tract [ 33 ]. Our previous studies also found that COS promoted the growth, metabolic activity, and metabolite concentration changes of probiotics represented by Akkermansia muciniphila by affecting specific populations in microbial groups; reduced the adhesion, invasion, and colonization of intestinal pathogens represented by Escherichia coli ; and inhibited the occurrence and development of enteritis, thereby maintaining intestinal health [ 34 , 35 ].…”
Section: Effects Of Functional Oligosaccharides On the Intestinal Bar...mentioning
confidence: 99%